2022
DOI: 10.1021/acs.orglett.2c03638
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Benzo[c][1,2]dithiol-3-ones via Acid-Promoted Denitrogenative Transannulation of Benzotriazinones

Abstract: An expedient synthesis of benzo [c][1,2]dithiol-3ones via metal-free denitrogenative transannulation of benzotriazinones is developed, which represents the first example of acidmediated heteroannulation of benzotriazinones. This newly discovered reactivity of benzotriazinones enables the streamline synthesis of diverse benzo[c][1,2]dithiol-3-ones in decent yields by using sodium sulfide as the sulfur source under simple reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Meanwhile, we also described trifluoroacetic acid-mediated ortho -hydroxylated benzamide synthesis from 1,2,3-benzotriazin-4­(3 H )-ones . More recently, acid-mediated heteroannulation of benzotriazinones using sodium sulfide to synthesize benzo­[ c ]­[1,2]­dithiol-3-ones was reported by the research group of Zhou …”
Section: Introductionmentioning
confidence: 97%
“…Meanwhile, we also described trifluoroacetic acid-mediated ortho -hydroxylated benzamide synthesis from 1,2,3-benzotriazin-4­(3 H )-ones . More recently, acid-mediated heteroannulation of benzotriazinones using sodium sulfide to synthesize benzo­[ c ]­[1,2]­dithiol-3-ones was reported by the research group of Zhou …”
Section: Introductionmentioning
confidence: 97%
“…Transformations of 1,2,3-benzotriazinones by transition-metal-catalyzed denitrogenative annulation with olefins/alkynes or allenes/isocyanides, cross-coupling with C-centered nucleophiles and metal-free displacement by heteroatom (P, O, S, and Se) reagents have proven to be effective to prepare heterocycles and ortho -substituted benzamides. We have recently reported nickel-catalyzed manganese-mediated cross-coupling of benzotriazinones with alkyl halides for the synthesis of ortho -alkylated benzamides in the presence of trimethylsilyl chloride (TMSCl) as an activator in a strong polar solvent, N,N -dimethylacetamide (DMA), increasing the pool size of aryl counterparts in the emerging transition metal-catalyzed cross electrophile couplings pioneered by Weix and Gong and co-workers .…”
Section: Introductionmentioning
confidence: 99%
“…Later, Wang and co-workers used Ir­(ppy) 3 as the photocatalyst to accomplish the denitrogenative ortho -selenylation of benzotriazinones to access ortho -selenylated benzamides . In 2022, Zhou et al reported an expedient synthesis of benzo­[ c ]­[1,2]­dithiol-3-ones via denitrogenative transannulation of benzotriazinones with Na 2 S as the sulfur source. By treating benzotriazinones in CF 3 COOH, Mannathan and co-workers introduced ortho -hydroxy groups under mild conditions .…”
mentioning
confidence: 99%